A Rare Case of Low-pressure Hydrocephalus After Skull Base Surgery. Issue 3 (August 2016) - Lin, Bon-Jour; Ma, Hsin-I
Abstract : Low-pressure hydrocephalus (LPH) after skull base surgery is rare. We report a 52-year-old man with sphenoidal planum meningioma who underwent a pterional approach for tumor excision. After surgery, consciousness disturbance and intraventricular hemorrhage with associated hydrocephalus were observed. Clinical expression revealed poor response to apparently adequate cerebrospinal fluid drainage through external ventricular drain and functioning ventriculoperitoneal shunt with persisted ventriculomegaly on brain computed tomography scans. A diagnosis of LPH was made, and then combination of external ventricular drain with subatmospheric drainage and endoscopic third ventriculostomy were performed. Finally, the patient recovered clear consciousness with recovery of normal ventricular size. This report highlights the postulated mechanism of LPH formation after skull base surgery and advocates some treatment options for this rare entity.